Impact of grape marc, as a partial replacer of sugar and wheat flour, on the bioaccessibility of polyphenols, technological, sensory, and quality properties of cake by mixture design approach - Bursa, Kubra; Isik, Goksen; Yildirim, Rusen Metin; Ozulku, Gorkem; Kian-Pour, Nasim; Toker, Omer Said; Palabiyik, Ibrahim; Gulcu, Mehmet (WALTER DE GRUYTER GMBH, 2022)
This investigation aimed to valorize grape marc (GM) in the formulation of cakes for ideal technological, nutritional and organoleptic properties. The GM (0-20%) was used for the partial substitution of wheat flour (40-50%) and sugar (40-50%). Total polyphenols in the cake samples, their post digestion, and bioaccessibility varied from 65.49-462.07; 13.34-608.62 mg GAE/g, and 23.42-315.47%, respectively. The values of the elastic modulus of the batter were higher than those of the viscous modulus, indicating the elastic behavior of the cakes. The hardness and springiness ranged from 2.20-4.22 N, and 0.85-0.98 mm, respectively. The results predicted by mixture design revealed that the samples including 50% wheat flour, 48.73% sugar, and 1.94% GM were the best formulation for the optimization of organoleptic properties. According to the results, GM can be used to develop cakes with a good nutritional composition as well as functional, sensory, and quality attributes at the industrial scale.
Keywords: cake; grape marc; mixture design; polyphenol; sensory properties; ANTIOXIDANT ACTIVITY; PHENOLIC-COMPOUNDS; DIETARY FIBER; SPONGE CAKE; POMACE; SOURDOUGH; DIGESTION; FRUIT; PEEL; Food Science & Technology